Pengaruh Kepemimpinan, Lingkungan Kerja, dan Disiplin Kerja terhadap Kinerja Karyawan pada Bumi Muwa Hotel Ubud - I Wayan Bina Candra Amertha; Wayan Sri Maitri (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
High-quality and professional human resources will be created if the company consistently develops and rewards employees for their performance. This study aims to determine the impact of leadership, work environment, and work discipline on employee performance at Bumi Muwa Hotel Ubud. The sampling technique used in this study was saturated sampling, with a sample size of 60 employees. Data were collected using observation, questionnaires, and documentation studies, processed using multiple linear regression analysis using SPSS version 26. Based on the analysis, this study shows that leadership has a positive and significant effect on employee performance at Bumi Muwa Hotel Ubud. This means that the better the leadership, the higher the employee performance. The work environment has a positive and significant effect on employee performance at Bumi Muwa Hotel Ubud. This means that a comfortable, safe, and conducive work environment can increase employee morale and performance in carrying out their duties and responsibilities. Work discipline has a positive and significant effect on employee performance at Bumi Muwa Hotel Ubud. This means that the higher the employee’s level of work discipline, the better their performance in carrying out their duties and responsibilities. Leadership, work environment, and work discipline have a positive and significant impact on employee performance at Bumi Muwa Hotel Ubud. This means that the implementation of good leadership, supported by a conducive work environment, and high work discipline can collectively improve employee performance optimally